From Asthma to AirBeat: Community-Driven Monitoring of Fine Particles and Black Carbon in Roxbury, Massachusetts. - Loh, Penn.; Sugerman-Brozan, Jodi.; Wiggins, Standrick.; Noiles, David.; Archibald, Cecelia. (Tufts University. Tisch Library., 2019)
Asthma is an ongoing environmental justice concern in Roxbury, an urban neighborhood of Boston, Massachusetts. Residents, especially local youth, were the first to investigate the potential links between high asthma rates and air pollution, particularly from diesel buses and trucks. A youth-led march for clean air and community air monitoring projects drew governmental and media attention to these problems. In 1998, a collaboration of environmental justice, government, and research groups came together to develop a real-time air pollution monitoring system known as AirBeat. This community-based participatory research project was designed to answer community questions about whether there are pollution "hot spots" in Roxbury and the degree to which diesel emissions are contributing to health problems. AirBeat measures and reports levels of PM2.5 (particulate matter with a mass median aerodynamic diameter ≤2.5 µm), ozone, and black carbon on an hourly basis. These data are accessible via a website, telephone hotline, and a flag warning system. AirBeat is successful because community residents and organizations participate as equal partners with an equitable share of funding. The project also promotes a community sense of ownership and pride. Dozens of youth have developed leadership and scientific skills. The media have extensively covered the project as a community victory. The data support the claim that Dudley Square in Roxbury is a hot spot for air pollution. This information is now being used to advocate for alternative fuel transit buses and other clean air measures. Finally, this project has strengthened community partnerships with research and governmental institutions.